Pengaruh dimensi equitas merek terhadap kepercayaan konsumen - Edy Purwanto; M. Munir Syam AR; Miftahol Arifin (Jurnal Riset Manajemen dan Bisnis, 2022)
This research aims to analyze and determine the accuracy of the dimensions of brand equity (brand awareness, perceived quality, and brand associations in influencing brand trust. This study examines instant noodle brands as research objects. The number of samples used was 170 respondents. The sample determination used was the purposive sampling technique. The data was collected by distributing questionnaires. In analyzing the data, it was carried out using multiple linear regression analysis. The results of this study indicate that the variables of brand awareness, perceived quality, and brand associations affect consumer trust. This research is expected to confirm the accuracy of the dimensions of brand equity in predicting consumer trust. The practical contribution of this research is that it can provide information to academics and practitioners about the application of brand equity dimensions in predicting consumer trust in instant noodles: indomie and mie sedaap.